Place of effective management and "place of business" : a critical analysis of whether or not these phrases (as used in the Income Tax Act and Companies Act respectively) should be aligned or have different meanings? - Kriel, Elsabe (Department of Finance and Tax, 2014)
Includes abstract. Includes bibliographical references (leaves 65-70).